2017
DOI: 10.1038/s41598-017-09064-w
|View full text |Cite|
|
Sign up to set email alerts
|

Facile single-stranded DNA sequencing of human plasma DNA via thermostable group II intron reverse transcriptase template switching

Abstract: High-throughput single-stranded DNA sequencing (ssDNA-seq) of cell-free DNA from plasma and other bodily fluids is a powerful method for non-invasive prenatal testing, and diagnosis of cancers and other diseases. Here, we developed a facile ssDNA-seq method, which exploits a novel template-switching activity of thermostable group II intron reverse transcriptases (TGIRTs) for DNA-seq library construction. This activity enables TGIRT enzymes to initiate DNA synthesis directly at the 3′ end of a DNA strand while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 61 publications
5
46
1
Order By: Relevance
“…Analysis of TGIRT-seq datasets obtained for fragmented UHRs or plasma DNA suggested that a major source of sequence bias is the DNA ligation step using the thermostable 5' App DNA/RNA ligase, which has a preference for A or C and against U/T at position -3 from the 3' end of the acceptor nucleic acid (Jackson et al 2014;Nottingham et al 2016;Wu and Lambowitz 2017). We noticed that the R2R adapter used currently for TGIRT-seq (denoted NTC based on its 3' end sequence) has a C-residue at position -3 from its 3' end, which favors the formation of R1R-R2R adapter dimers during the ligation step ( Fig.…”
Section: A Single Nucleotide Change In the R2r Adapter Strongly Decrementioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of TGIRT-seq datasets obtained for fragmented UHRs or plasma DNA suggested that a major source of sequence bias is the DNA ligation step using the thermostable 5' App DNA/RNA ligase, which has a preference for A or C and against U/T at position -3 from the 3' end of the acceptor nucleic acid (Jackson et al 2014;Nottingham et al 2016;Wu and Lambowitz 2017). We noticed that the R2R adapter used currently for TGIRT-seq (denoted NTC based on its 3' end sequence) has a C-residue at position -3 from its 3' end, which favors the formation of R1R-R2R adapter dimers during the ligation step ( Fig.…”
Section: A Single Nucleotide Change In the R2r Adapter Strongly Decrementioning
confidence: 99%
“…Here, we used the previously determined ligation biases of the thermostable 5' App RNA/DNA ligase (Jackson et al 2014;Nottingham et al, 2016;Wu and Lambowitz 2017) to design an R2/R2R adapter with just a single nucleotide change that dramatically decreases the formation of adapter dimers, thereby improving the recovery of miRNA sequences and enabling the construction of TGIRT-seq libraries from smaller amounts of starting material. Additionally, using a miRNA reference set containing an equimolar mix of 962 human miRNAs, we systematically analyzed 5'-and 3'-end biases in TGIRT-seq introduced by the thermostable 5' App RNA/DNA ligase and template switching, respectively, and developed biochemical and computational methods for ameliorating these biases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, the current ssDNA-based methods are still restricted by some limitations such as input DNA dephosphorylation, isolation with biotin-magnetic beads and dependence on special ligase (e.g. CircLigase II) 15,17,18 or retroviral reverse transcriptase (e.g. DNA SMART ChIP-seq Kit, Clontech).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the R2 element RT (33,34), group II intron RTs do not need to be actively elongating to template switch and can do so directly from synthetic RNA template/DNA primer substrates with a single-nucleotide (1-nt) 3'-DNA overhang that base pairs with the 3' nucleotide of an RNA acceptor (6). This reaction enables the precise attachment of 3' RNA-seq adapters to target RNAs or DNAs in a single step without tailing or ligation (8,9,40).…”
Section: Introductionmentioning
confidence: 99%